Junior High School Students’ Difficulties in Writing Descriptive Text - Syifa, Qorina Aulia; Baekani, Abdul Kodir Al-; Srisudarso, Mansyur (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Writing is one of the skills that must be possessed by students when learning English. It is one way of expressing ideas, feelings, thoughts, even arguments and knowledge into a piece of paper. Descriptive text is a text which purpose is to describe someone, a place, or something. Students considered writing descriptive text is difficult to do because it is done in English which is a foreign language for them. This research aimed to understand students’ difficulty in writing descriptive text and the causes. This research was using the narrative inquiry method in one of Junior High School in Karawang with a total of five eight-grade students as the participants. The data was collected through a structured personal interview with an interview guideline as the instruments and analyzed based on Miles & Huberman (1994): data reduction, data display, and drawing conclusion/verification. The findings showed that one of the biggest factors causes students to have difficulty in writing descriptive text is their dislike of the English language itself and even though the students know about writing descriptive in general, it doesn’t make them want to learn about it. Also, there are several difficulties that the students face when they are asked to write descriptive texts such as they do not understand grammar, they have very little vocabulary, they do not know the meaning of each vocabulary, and they have difficulty constructing sentences when write descriptive text which cause by their dislike on learning English, teaching techniques that make them bored, feeling lazy in learning grammar and vocabulary, and difficulty in reading and translating vocabulary due to lack of vocabulary they have.